Discourse and discursive expressions of the teaching staff How are gender stereotypes reproduced? - Vargas Huanca, Georgette (2019)
The research carried out on how gender stereotypes are reproduced in the EBR teacher-student relationship has as its object of study the oral discourse of male and female teachers, which does not explain how gender stereotypes continue to be reproduced in schools despite of the care that teachers, aware of this problem, give to their hierarchical relationship with students. The objective of this article is to argue that if we consider the teacher-student relationship as a habitus, then the reproduction of gender stereotypes in schools is evident not only in the oral discourse of teachers, but also in diverse discursive expressions.